2019
DOI: 10.1210/clinem/dgz099
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Comparison of Afirma GEC and GSC for the Assessment of Cytologically Indeterminate Thyroid Nodules

Abstract: Context Molecular tests have improved the accuracy of preoperative diagnosis of indeterminate thyroid nodules. The Afirma Gene Sequencing Classifier (GSC) was developed to improve the specificity of the Gene Expression Classifier (GEC). Independent studies are needed to assess the performance of GSC. Objective The aim was to compare the performance of GEC and GSC in the assessment of indeterminate nodules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 14 publications
7
80
1
Order By: Relevance
“…Compared with the previous version, the new test correctly classifies more indeterminate nodules as benign and displays improved specificity (68.3%) and positive predictive value (47.1%), with a sensitivity of 91.1% and a negative predictive value of 96.1% ( 67 ). It is expected to further reduce the frequency of diagnostic surgery, based on the results of independent studies ( 72-74 ). In short, the ThyroSeq and Afirma assays currently have positive and negative predictive values that make them suitable for use in both rule-in and rule-out testing.…”
Section: What To Do With Indeterminate Results?mentioning
confidence: 99%
“…Compared with the previous version, the new test correctly classifies more indeterminate nodules as benign and displays improved specificity (68.3%) and positive predictive value (47.1%), with a sensitivity of 91.1% and a negative predictive value of 96.1% ( 67 ). It is expected to further reduce the frequency of diagnostic surgery, based on the results of independent studies ( 72-74 ). In short, the ThyroSeq and Afirma assays currently have positive and negative predictive values that make them suitable for use in both rule-in and rule-out testing.…”
Section: What To Do With Indeterminate Results?mentioning
confidence: 99%
“…This implies an effort to develop US RSSs able to intercept FTC and MTC cases. On the other hand, a great effort is underway in validating molecular tests to improve cytological diagnosis [42][43][44][45]. In the meantime, international guidelines have sped up this process by promoting the potential of molecular tests in clinical practice [12,41].…”
Section: Discussionmentioning
confidence: 99%
“…For the Afirma-GSC, San Martin and colleagues found that the second generation test has a higher specificity (94 vs. 60%) while retaining similar negative predictive value (96.3 vs. 98.6%) compared to the GEC. This resulted in improved performance within specimens with Hürthle cell cytology, improved overall benign call rate of 68% ( vs. 41%) and a decrease in surgery rate from 48 to 35% for the population as a whole ( 36 ). Wei and colleagues have documented that the benign call rate for GSC is considerably higher than GEC (66.7 vs. 45.4%), and Endo and colleagues have reported a benign call rate of 88.8 vs. 25.7% for GSC vs. GEC for samples with Hürthle cells ( 37 , 38 ).…”
Section: Diagnostic Utilitymentioning
confidence: 99%
“…Prospective studies assessing the impact of these tests on the rate and appropriateness of surgical intervention are lacking, and most of the information is gleaned from retrospective data only. Moreover, many of the series suggesting that implementation of molecular testing leads to reduction in number of surgeries are correlative in nature, i.e., they show that fewer surgeries were done during period of molecular testing use compared to historical time period when testing was not used, but they do not directly show a causal effect at the individual patient/nodule level ( 36 , 39 , 42 ).…”
Section: Impact On Surgical Practicementioning
confidence: 99%